PENGARUH KEPEMILIKAN INSTITUSIONAL DAN VARIABEL KINERJA KEUANGAN TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Meita Putri Anggi Asari; Agung Juliarto (Diponegoro Journal of Accounting, 2023)
The study aims to examine whether institutional ownership and financial performance variables have an impact on the wide disclosure of Corporate Social Responsibility on corporate basic materials. The dependent variable in this study is a wide disclosure of Corporate Social Responsibility measured using the dummy variable.Independent variable in this study is institutional ownership, leverage, liquidity, and profitability.The study has a population of 95 basic materials companies registered in the period 2020-2021, While the sample has been used by 24 companies for two years, The number of samples used in this study was 48 observations.The study uses secondary data from the financial reports of the company’s basic materials listed on the Indonesian stock exchange for 2020-2021.The research hypothesis testing is performed using double linear regression analysis and SPSS 23 software.This study results statistics shows that institutional ownership having influence positively and significantly to wide disclosure of corporate social responsibility, leverage to have the positive but not significant to wide disclosure of corporate social responsibility, liquidity having influence positively and significantly to wide disclosure of corporate social responsibility, and profitability have the negative and significantly to wide disclosure of Corporate Social Responsibility